Reassessment of the Listeria monocytogenes pan-genome reveals dynamic integration hotspots and mobile genetic elements as major components of the accessory genome - Kuenne, Carsten; Billion, André; Abu Mraheil, Mobarak; Strittmatter, Axel; Daniel, Rolf; Goesmann, Alexander; Barbuddheand , Sukhadeo; Hain, Torsten; Chakraborty, Trinad; Justus Liebig University Giessen (My University, 2013)
Background: Listeria monocytogenes is an important food-borne pathogen and model organism for host-pathogeninteraction, thus representing an invaluable target considering research on the forces governing the evolution ofsuch microbes. The diversity of this species has not been exhaustively explored yet, as previous efforts have focusedon analyses of serotypes primarily implicated in human listeriosis. We conducted complete genome sequencing of11 strains employing 454 GS FLX technology, thereby achieving full coverage of all serotypes including the firstcomplete strains of serotypes 1/2b, 3c, 3b, 4c, 4d, and 4e. These were comparatively analyzed in conjunction withpublicly available data and assessed for pathogenicity in the Galleria mellonella insect model.Results: The species pan-genome of L. monocytogenes is highly stable but open, suggesting an ability to adapt tonew niches by generating or including new genetic information. The majority of gene-scale differences representedby the accessory genome resulted from nine hyper variable hotspots, a similar number of different prophages,three transposons (Tn916, Tn554, IS3-like), and two mobilizable islands. Only a subset of strains showed CRISPR/Casbacteriophage resistance systems of different subtypes, suggesting a supplementary function in maintenance ofchromosomal stability. Multiple phylogenetic branches of the genus Listeria imply long common histories of strainsof each lineage as revealed by a SNP-based core genome tree highlighting the impact of small mutations for theevolution of species L. monocytogenes. Frequent loss or truncation of genes described to be vital for virulence orpathogenicity was confirmed as a recurring pattern, especially for strains belonging to lineages III and II. Newcandidate genes implicated in virulence function were predicted based on functional domains and phylogeneticdistribution. A comparative analysis of small regulatory RNA candidates supports observations of a differentialdistribution of trans-encoded RNA, hinting at a diverse range of adaptations and regulatory impact.Conclusions: This study determined commonly occurring hyper variable hotspots and mobile elements as primaryeffectors of quantitative gene-scale evolution of species L. monocytogenes, while gene decay and SNPs seem torepresent major factors influencing long-term evolution. The discovery of common and disparately distributedgenes considering lineages, serogroups, serotypes and strains of species L. monocytogenes will assist in diagnostic,phylogenetic and functional research, supported by the comparative genomic GECO-LisDB analysis server(http://bioinfo.mikrobio.med.uni-giessen.de/geco2lisdb).
Keywords: ddc:610